2020
DOI: 10.2337/dc19-1507
|View full text |Cite
|
Sign up to set email alerts
|

Plasma N-Glycans as Emerging Biomarkers of Cardiometabolic Risk: A Prospective Investigation in the EPIC-Potsdam Cohort Study

Abstract: Plasma protein N-glycan profiling integrates information on enzymatic protein glycosylation, which is a highly controlled ubiquitous posttranslational modification. Here we investigate the ability of the plasma N-glycome to predict incidence of type 2 diabetes and cardiovascular diseases (CVDs; i.e., myocardial infarction and stroke). RESEARCH DESIGN AND METHODSBased on the prospective European Prospective Investigation of Cancer (EPIC)-Potsdam cohort (n 5 27,548), we constructed case-cohorts including a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…A lower relative abundance of simple biantennary N-glycans and a higher abundance of branched, galactosylated and sialylated complex N-glycans were increased both in type 1 [28] and type 2 [27] diabetes, and similar trends with increased levels of complex N-glycans (GP12, GP16 and GP22) were seen for higher UACR and greater annual loss of eGFR [26,28]. Recently, in the prospective European Prospective Investigation of Cancer (EPIC)-Potsdam cohort (n = 27,548), the increased levels of complex N-glycans, GP5 in women and GP16, GP23, and GP29 in men, improved the accuracy of risk production score for CVD [29].…”
Section: -Year Risk Classi Cation Ability Of Urinary Glycan Binding mentioning
confidence: 68%
See 1 more Smart Citation
“…A lower relative abundance of simple biantennary N-glycans and a higher abundance of branched, galactosylated and sialylated complex N-glycans were increased both in type 1 [28] and type 2 [27] diabetes, and similar trends with increased levels of complex N-glycans (GP12, GP16 and GP22) were seen for higher UACR and greater annual loss of eGFR [26,28]. Recently, in the prospective European Prospective Investigation of Cancer (EPIC)-Potsdam cohort (n = 27,548), the increased levels of complex N-glycans, GP5 in women and GP16, GP23, and GP29 in men, improved the accuracy of risk production score for CVD [29].…”
Section: -Year Risk Classi Cation Ability Of Urinary Glycan Binding mentioning
confidence: 68%
“…The high throughput plasma or serum N-glycan pro ling studies using hydrophilic interaction liquid chromatography (HILIC) of peptide-N-glycosidase F digested and uorescently labelled N-glycans was reported and 46 N-glycan peaks (GP1-GP46) were demonstrated [25][26][27][28][29]. In the patients with normo-and hyperglycemia during acute in ammation, the comparison of N-glycan pro le demonstrated that increased branched, galactosylated, and sialylated tri-and tetraantennary N-glycans are associated with development of type 2 diabetes [25].…”
Section: -Year Risk Classi Cation Ability Of Urinary Glycan Binding mentioning
confidence: 99%
“…Recent studies demonstrated that some serum metabolites, ratios of several traditional metabolic parameters, and adipokines could have closed relationship with the cardiometabolic risk. Serum glycans could improve type 2 diabetes and CVD prediction beyond established risk markers [44]. TG : HDL-C ratio and triglyceride-glucose index are all reported to be associated with the cardiometabolic disorders [45,46].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…Besides age-related changes, specific IgG glycosylation patterns have been already associated with CVD risk score and subclinical atherosclerosis in two large independent UK cohorts [13]. Moreover, a prospective follow-up of the EPIC-Potsdam cohort confirmed that changes in plasma N-glycome composition are predictive of future CVD events, with comparable predictive power to the American Heart Association (AHA) score in men and even better predictive power in women [14]. The link between a proinflammatory IgG N-glycome and hypertension has also been extensively studied [15-17], and similar IgG glycosylation patterns were associated with increased body mass index (BMI) and measures of central adiposity [18,19].…”
Section: Introductionmentioning
confidence: 99%